2022
DOI: 10.31620/jccc.06.22/02
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks Influence in Choosing a Tourist Destination

Abstract: The use of social media is having an increasingly positive impact on tourism activities and the information available on social networks. The aim of this study is to investigate the opinions of social network users regarding their perceptions of social network use, social network communication, and social network information that influence the decision-making process of potential tourists when choosing a destination. The survey was conducted using an online questionnaire and the collected data was processed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…According to them, younger tourists and those who are more educated use e-services more intensively and will continue to use them as they get older. Likewise, earlier research (Amarao & Duearte, 2017;Tanković et al, 2022) showed that women are the ones who use more and participate more often in research related to social networks. As in previous research (Süli & Martyin-Csamangó, 2020;Tešin et al, 2022), the results of this research agree that the most frequently used social networks are Facebook, Instagram, and YouTube, as well as that respondents use social networks several times a day (Tanković et al, 2022).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…According to them, younger tourists and those who are more educated use e-services more intensively and will continue to use them as they get older. Likewise, earlier research (Amarao & Duearte, 2017;Tanković et al, 2022) showed that women are the ones who use more and participate more often in research related to social networks. As in previous research (Süli & Martyin-Csamangó, 2020;Tešin et al, 2022), the results of this research agree that the most frequently used social networks are Facebook, Instagram, and YouTube, as well as that respondents use social networks several times a day (Tanković et al, 2022).…”
Section: Discussionmentioning
confidence: 85%
“…Likewise, earlier research (Amarao & Duearte, 2017;Tanković et al, 2022) showed that women are the ones who use more and participate more often in research related to social networks. As in previous research (Süli & Martyin-Csamangó, 2020;Tešin et al, 2022), the results of this research agree that the most frequently used social networks are Facebook, Instagram, and YouTube, as well as that respondents use social networks several times a day (Tanković et al, 2022). Respondents most often use social networks for fun and relaxation, while to a lesser, but not negligible degree, they serve as a source of information.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The strategic use of social media for tourism marketing in India is continuously evolving with promotion of new web applications to develop partnership among the stakeholders. The state tourism bodies of various states like Madhya Pradesh, Odisha, Arunachal Pradesh, Gujrat, Himachal Pradesh, including Incredible India campaign, have amplified their voice on social media to leverage tourism domestically, with a strong recommendation from various research works emphasizing influence of social media on decision making and travel choices (Karatsoli &Nathanail, 2020;Gupta, 2022;Tanković et al, 2022). The Incredible India campaign by the government of India registered huge viewers online and spurred in foreign tourists visitors (Mishra & Sajnani, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This has complemented the other web-based means of communication used by the sales or channel management. Tanković, Bilić, and Sohor, [36] (p. 2), in their recent study of the role of social networks in tourist destination choice concluded that "the use of social media is having an increasingly positive impact on tourism activities and the information available on social networks". For example, customer enquiries and order confirmation may come from online travel agencies (such as Expedia, LastMinute.com, Booking.com), with onward communication with customers being conducted via social media or email.…”
Section: Literature Reviewmentioning
confidence: 99%